2008
DOI: 10.1017/s1366728908003416
|View full text |Cite
|
Sign up to set email alerts
|

Phonological short-term memory, working memory and foreign language performance in intensive language learning

Abstract: In our research we addressed the question what the relationship is between phonological short-term and working memory capacity and performance in an end-of-year reading, writing, listening, speaking and use of English test. The participants of our study were 121 secondary school students aged 15-16 in the first intensive language training year of a bilingual education program in Hungary. The participants performed a non-word repetition test and took a Cambridge First Certificate Exam. Fifty students were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
204
4
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(266 citation statements)
references
References 45 publications
28
204
4
10
Order By: Relevance
“…Learners may need to be using considerable attentional and memory resources to access and retrieve words, and to give messages their syntactic and morphophonological shape, to a point that differences in working memory may not matter. Our results therefore suggest that for working memory to pose an advantage in L2 performance a certain level of proficiency needs to be achieved, results which are in contrast with those of Kormos and Sáfár (2008). Therefore, more research is needed that looks at the relationship between working memory and proficiency level with higher control of the latter.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Learners may need to be using considerable attentional and memory resources to access and retrieve words, and to give messages their syntactic and morphophonological shape, to a point that differences in working memory may not matter. Our results therefore suggest that for working memory to pose an advantage in L2 performance a certain level of proficiency needs to be achieved, results which are in contrast with those of Kormos and Sáfár (2008). Therefore, more research is needed that looks at the relationship between working memory and proficiency level with higher control of the latter.…”
Section: Discussionmentioning
confidence: 75%
“…The results in this study suggest that there is no correlation between working memory and overall attainment, and are in line with those of Mizera (2006) who found no correlation between a general proficiency test in L2 Spanish and working memory scores. In the first place, the present study tested the proficiency of learners at a given point after years of learning the language and was therefore not looking at gains over time as in Kormos and Sáfár (2008). It is feasible to believe that differences in working memory alone, which as we saw in the literature review have been shown to affect the rate of acquisition, cannot explain the different levels of attainment, and should therefore be combined with other variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working memory (WM) is associated with L2 reading, speaking, vocabulary and listening abilities (Kormos & Sáfár, 2008). However, among the selected papers only a few articles took into account WM in their analysis of music-L2 transfer (Herrera et al, 2011;François et al, 2012;Posedel et al, 2011;Slevc & Miyake, 2006).…”
Section: The Role Of Working Memory In the Musiclanguage Transfer Effmentioning
confidence: 99%
“…Further research has centered on multi-sensory instruction incorporating explicit phonological teaching (Ganschow & Sparks, 1995), and a two-year study of at-risk students indicated that a multi-sensory approach promoted performance comparable to peers instructed with traditional methods (Sparks et al, 1998). Because of demands in working memory and diverse functioning of the CNS which can affect second language learning (Kormos & Safar, 2008;Palladino & Cornoldi, 2004), multi-sensory approaches have been promoted by Dal (2008) and Sousa (2001) and supported by the research of Amend et al (2009).…”
Section: Multi-sensory Approachesmentioning
confidence: 99%